Investigation of smartphone use characteristics underlying problematic smartphone use by dense longitudinal smartphone tracking - Wazulin, Lea; Jamin, Matthias; Andone, Ionut; Blaszkiewicz, Konrad; Reinhard, Iris; Eibes, Mark; Wolf, Robert Christian; Kasem, Qais; Markowetz, Alexander; Leménager, Tagrid; Bach, Patrick (Computers in human behavior, 2025)
Growing evidence suggests problematic smartphone use can lead to impaired mental health and quality of life. We conducted a 60-day longitudinal smartphone tracking study using an app capturing daily smartphone use. 186 individuals were enrolled and classified as problematic (PSUs, n = 86) or unproblematic smartphone users (USUs, n = 100), based on the Smartphone Addiction Scale - Short Version (SAS-SV). Sociodemographic data, mental health and quality of life were assessed at baseline. Using linear mixed effects models (LMMs), primary analyses examined the effects of time, group (PSU vs. USU), gender, and time × group interactions on daily total smartphone and app category use i.e. communication, social and gaming apps. Overall, participants used their smartphones for 3.7 h per day, with higher daily use in PSUs (4.2 h) compared to USUs (3.3 h). These group differences were also present in daily use of communication and social apps, alongside a significant effect of gender on daily total use of any app (F(1,189) = 5.06, p = 0.026). Secondary gender-stratified analyses showed that male PSUs used their smartphones significantly more than USUs in both total (F(1,106.15) = 12.06, p < 0.001) and social app use (F(1,105.44) = 9.23, p = 0.003). In females, the only group difference found was in the communication app category, with higher daily use in PSUs (F(1,97.34) = 6.50, p = 0.012). Nevertheless, PSUs of both genders reported lower quality of life and higher levels of depressiveness at baseline, which significantly correlated with PSU severity (all r > 0.22, all p < 0.041).